WHETHER CO-ADMINISTRATION OF GARLIC HAS NEGATIVE INFLUENCE ON SCUTELLARIA BAICALENSIS GEORGI IN TREATING MODELS RATS WITH PELVIC INFLAMMATION? - Zhou, Jue; Qu, Fan; Yu, Yongping; Nan, Rui (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
The research was to explore whether co-administration of garlic has negative influence on Scutellaria baicalensis Georgi (Scutellaria baicalensis) in treating models rats with pelvic inflammation. Twelve model rats were randomized into a Scutellaria baicalensis group and a Scutellaria baicalensis+garlic group with six in each group for pharmacokinetic analysis. Twenty-four rats were randomized into a Scutellaria baicalensis group, a Scutellaria baicalensis+garlic group, a model control group and a normal control group with six rats in each group for detecting the serum levels of tumor necrosis factor-alpha (TNF-α) and interleukin 6 (IL-6) with enzyme-linked immunosorbent assay (ELISA). The results showed that in the Scutellaria baicalensis group, the maximum concentration (Cmax) of baicalin, area under the plasma concentration–time curve (AUC) and the time to Cmax (Tmax) were significantly higher and apparent clearance (CL/F) were significantly lower than those of Scutellaria baicalensis+garlic group. The serum levels of TNF-α and IL-6 in the Scutellaria baicalensis group were both significantly lower than Scutellaria baicalensis+garlic group. It was then concluded that garlic not only had negative influence on the absorption of active compounds in Scutellaria baicalensis, but decreased the curative effects of Scutellaria baicalensis in treating model rats with pelvic inflammation. Garlic should not be co-administered with Scutellaria baicalensis.